2008
DOI: 10.1017/s0022112008002073
|View full text |Cite
|
Sign up to set email alerts
|

Feedback shear layer control for bluff body drag reduction

Abstract: Drag reduction strategies for the turbulent flow around a D-shaped body are examined experimentally and theoretically. A reduced-order vortex model describes the interaction between the shear layer and wake dynamics and guides a path to an efficient feedback control design. The derived feedback controller desynchronizes shear-layer and wake dynamics, thus postponing vortex formation. This actuation is tested in a wind tunnel. The Reynolds number based on the height of the body ranges from 23000 to 70000. We ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
172
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(192 citation statements)
references
References 72 publications
(87 reference statements)
18
172
1
1
Order By: Relevance
“…In configuration B, with the jet acting at 45 degrees upwards, at the point of separation it is suggested that the size of the wake is increased by deflecting the shear layer upwards. Some theories regarding the influence of wake size on resultant body forces predict that a stretched wake will create increased base pressures by moving vortex structures away from the base surface and so reduced body drag forces (Pastoor 2008;Bearman 1983). Other published work (Rounmeas 2008) suggests that a reduction in wake size will increase base pressures and create lower drag forces.…”
Section: Balance Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In configuration B, with the jet acting at 45 degrees upwards, at the point of separation it is suggested that the size of the wake is increased by deflecting the shear layer upwards. Some theories regarding the influence of wake size on resultant body forces predict that a stretched wake will create increased base pressures by moving vortex structures away from the base surface and so reduced body drag forces (Pastoor 2008;Bearman 1983). Other published work (Rounmeas 2008) suggests that a reduction in wake size will increase base pressures and create lower drag forces.…”
Section: Balance Resultsmentioning
confidence: 99%
“…8 are a result of modification to this lower structure, and its interaction with the base surface in addition to the global reduction in wake size. In effect, the benefits of stretching the wake to move vortices further away from the base outlined by Bearman (1983) and Pastoor (2008), are, in this instance, created by the downward blowing of the jet weakening the lower vortex structure. The weakening of this structure is shown in the reduction in the magnitude of vorticity of the structure, comparing Fig.…”
Section: Pivmentioning
confidence: 99%
See 1 more Smart Citation
“…For flow control of the bluff body, drag reduction is closely associated with the shear layer instability [25]. To analyze the flow control mechanism relevant to the shear layer instability, Figure 5 shows the instantaneous iso-contours of local Mach number M l .…”
Section: Self-sustained Oscillations Along the Shear Layermentioning
confidence: 99%
“…From the control perspective, in order to increase the base pressure and reduce the drag, the alternating character of the wake has to be mitigated or delayed [25]. The wake instability is closely associated with the shear-layer instability, and suppression of vortex roll-up inside the shear layer is enabler to increase the base pressure.…”
Section: Characteristics Of Separated Shear-layer Evolutionmentioning
confidence: 99%